Diagnóstico de la gestión pública en la situación turística del Manglar la Boca, San Jacinto 2023 - Vélez Vélez, Julia Lilibeth (2025)
The research focuses on the diagnosis of the tourist offer, the analysis of public management and the design of marketing strategies to promote sustainable tourism in La Boca Mangrove, San Jacinto. In the first phase, a diagnosis was carried out that allowed identify significant deficiencies in tourism infrastructure and the quality of services, which affects the tourist experience and local economic development, the second phase focused on the analysis of the performance of public management, revealing a lack of coordination between the local authorities and the community, as well as the absence of clear policies that promote sustainability and community participation in the tourist management of the mangrove, in the third phase, marketing strategies were designed aimed at improving the promotion of the mangrove as an eco-tourist destination. , taking advantage of its biodiversity and the cultural value of the region, despite the initial efforts, it is concluded that a greater commitment on the part of the authorities and better preparation in digital marketing is necessary to attract a greater number of visitors. The results highlight the importance of improving infrastructure and public policies to ensure sustainable tourism development that benefits both the community and the ecosystem.